Tikkana cēsina mārpulu, aucityapu tīrpulu : Virāṭōdyōga parvamulu - Sumatī Narēndra, Pi., 1950- (Bālakrṣṇa Bhārati, 1982)
Study on additions and omissions made and their propriety in the Telugu rendering of Virāṭaparva and Udyogaparva of the Mahābhārata by Tikkana, 1220-1300, Telugu poet.